Mary McAuliffe. Twilight of the Belle Epoque: The Paris of Picasso, Stravinsky, Proust, Renault, Marie Curie, Gertrude Stein, and Their Friends through the Great War. Lanham, MD: Rowman and Littlefield. 2014. vii + 418 pp. - Eric Martone (Studies in 20th & 21st Century Literature, 2015)
Review of Mary McAuliffe. Twilight of the Belle Epoque: The Paris of Picasso, Stravinsky, Proust, Renault, Marie Curie, Gertrude Stein, and Their Friends through the Great War. Lanham, MD: Rowman and Littlefield. 2014. vii + 418 pp.
Keywords: French culture; Paris; Belle Epoque; World War I